2019
DOI: 10.1103/physrevc.99.065806
|View full text |Cite
|
Sign up to set email alerts
|

First experimental constraint on the Os191(n,γ) reaction rate relevant to s -process nucleosynthesis

Abstract: The nuclear level density and γ-decay strength of 192 Os have been extracted using particle-γ coincidence data from the 192 Os (α, α γ) 192 Os reaction by means of the Oslo method. The level density is found to be a rather smooth function of excitation energy, approximately following the constant temperature model. The γ-decay strength is compared to photoneutron cross-section data above the neutron separation energy, and to E1 and M1 strengths for nuclei in this mass region derived from primary transitions f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…In this work, we compare theoretical values to the semiexperimental values for nuclei in the same mass region as 127 Sb. Thus, we apply a similar strategy to the one in Kullmann et al [27], where D 0 values for the neighboring isotopes of Sn, Sb, and Te (corresponding to Z = 50, 51, and 52, respectively) from both the Atlas of Neutron Resonances [28] and the Reference Input Parameter Library [29] were used to calculate ρ(S n ). These values are then compared to the theoretical ρ(S n ) estimates using the global parametrization of Ref.…”
Section: Normalization and Uncertainty Propagation A Normalization Of...mentioning
confidence: 99%
“…In this work, we compare theoretical values to the semiexperimental values for nuclei in the same mass region as 127 Sb. Thus, we apply a similar strategy to the one in Kullmann et al [27], where D 0 values for the neighboring isotopes of Sn, Sb, and Te (corresponding to Z = 50, 51, and 52, respectively) from both the Atlas of Neutron Resonances [28] and the Reference Input Parameter Library [29] were used to calculate ρ(S n ). These values are then compared to the theoretical ρ(S n ) estimates using the global parametrization of Ref.…”
Section: Normalization and Uncertainty Propagation A Normalization Of...mentioning
confidence: 99%
“…The NLD and PSF are key ingredients in Hauser-Feshbach theory [66,67] to calculate nuclear reaction rates, for example using TALYS [68]. This has recently been done for the 191 Os(n,γ ) [69] and 126 Sb(n,γ ) [70] reactions. By measuring the NLD and PSF in charged-particle induced reactions, it is possible to constrain calculations of neutron-capture reaction rates in cases where direct (n,γ ) measurements are not feasible.…”
Section: Nuclear Level Density and Photon Strength Functions Using Th...mentioning
confidence: 99%
“…Using the data of Renstrøm et al [16], a very good agreement with the direct (n, γ ) data was found. Furthermore, for the s-process branching at the unstable 191 Os, Kullmann et al [17] provided experimental support to the adopted value of the KADoNiS database [18]. In the near future, (α, pγ ) reactions will be applied to access moderately neutron-rich nuclei of great importance for the i process, while at the same time bridging the gap towards r -process nuclei that will be studied at large radioactive-beam facilities.…”
Section: Nuclear Astrophysics: Heavy-element Nucleosynthesismentioning
confidence: 99%
“…[16]). c Deduced (n, γ ) Maxwellian-averaged cross section (MACS) of the s-process branch-point nucleus 191 Os from 192 Os(α, α γ ) data measured at OCL [17], compared to the KADoNiS recommended MACS [18] (modified from Ref. [17])…”
Section: Recent Highlight: Radiative Width Of the Hoyle Statementioning
confidence: 99%